2018
DOI: 10.1101/431569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Straightjacket/α2δ3deregulation is associated with cardiac conduction defects in Myotonic Dystrophy type 1

Abstract: Cardiac conduction defects decrease life expectancy in myotonic dystrophy type 1 (DM1), a complex toxic CTG repeat disorder involving misbalance between two RNAbinding factors, MBNL1 and CELF1. How this pathogenic DM1 condition translates into cardiac conduction disorders remains poorly understood. Here, we simulated MBNL1 and CELF1 misbalance in the Drosophila heart and identified associated gene deregulations using TU-tagging based transcriptional profiling of cardiac cells. We detected deregulations of seve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The main cardiac dysfunctions associated with DM1 correspond to conduction defects [43] with potentially fatal ventricular and/or atrial arrhythmias [44] and mechanical diastolic and/or systolic dysfunction that can lead to combined systolic and diastolic heart failure [45]. Importantly, Drosophila DM1 models have reproduced all these cardiac disorders [46,47].…”
Section: Drosophila Could Serve As a Model Organism For Dm1mentioning
confidence: 99%
See 3 more Smart Citations
“…The main cardiac dysfunctions associated with DM1 correspond to conduction defects [43] with potentially fatal ventricular and/or atrial arrhythmias [44] and mechanical diastolic and/or systolic dysfunction that can lead to combined systolic and diastolic heart failure [45]. Importantly, Drosophila DM1 models have reproduced all these cardiac disorders [46,47].…”
Section: Drosophila Could Serve As a Model Organism For Dm1mentioning
confidence: 99%
“…The data analysis revealed that the cardiac disorders observed in these DM1 models are the result of deregulation of genes involved in cellular calcium level and cardiac conduction. Among them are: inactivation no afterpotential D ( inaD ), syntrophin-like 1 ( syn1 ), Rad , Gem/Kir family member 2 ( Rgk2 ) and straightjacket ( stj ), all conserved in humans [47]. In particular, increased expression of stj , ortholog of CACNA2D3 in human, which encodes a regulatory subunit of a voltage-gated calcium channel CACNA1C/Cav1.2 was found to influence cardiac contractions.…”
Section: Identification Of New Mechanisms Underlying Dm1 Using Dromentioning
confidence: 99%
See 2 more Smart Citations